Analysis of the Leading Sector and the Effect of the Economic Growth: a Case Study in Pakpak Bharat Regency, Indonesia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
Pakpak Bharat Regency is an area with the lowest Gross Regional Domestic Product and Income percapita from 33 regency/city in North Sumatera Province. Because of this problem, to be important to know how the base sectors can improve the economy of Pakpak Bharat Regency. In this research, the study aims: (1) To know the base sectors in the economy of Pakpak Bharat Regency (2) To know the sector clasification of Gross Regional Domestic Product (GRDP) in Pakpak Bharat Regency (3) To know how the base sectors effect the Gross Regional Domestic Product of Pakpak Bharat Regency. The data used in this study is secondary data and readings related to research. The tests used in this study are Klassen Typology, Location Quotient, and Least Square test. The research finds that: (1) the economics of Pakpak Bharat Regency is divided into several quadrants, is advanced and rapidly growing sectors (Quadrant I), advanced but depressed sectors (Quadrant II), potential sector (Quadrant III), and lagging sector (Quadrant IV). (2) sectors classified as advanced sectors in Quadrant I and Quadrant II (amounting to 4 sectors) are basic sectors in Pakpak Bharat Regency with LQ>1. (3) there is a positive and significant influence between the base sector on the GRDP of Pakpak Bharat Regency.